Focal dose escalation using FDG-PET-guided intensity-modulated radiation therapy boost for postoperative local recurrent rectal cancer: a planning study with comparison of DVH and NTCP - Jingu, Keiichi; Ariga, Hisanori; Kaneta, Tomohiro; Takai, Yoshihiro; Takeda, Ken; Lindel, Katja; Narazaki, Kakutaro; Metoki, Takahiro; Fujimoto, Keisuke; Umezawa, Rei; Ogawa, Yoshihiro; Nemoto, Kenji; et al. (BMC cancer, 2010)
To evaluate the safety of focal dose escalation to regions with standardized uptake value (SUV) >2.0 using intensity-modulated radiation therapy (IMRT) by comparison of radiotherapy plans using dose-volume histograms (DVHs) and normal tissue complication probability (NTCP) for postoperative local recurrent rectal cancer
Gesehen am 28.08.2023